Autograft cellular composition and outcome in myeloma patients: Results of the prospective multicenter GOA study - Turunen Antti; Silvennoinen Raija; Partanen Anu; Valtola Jaakko; Siitonen Timo; Putkonen Mervi; Sankelo Marja; Pyorälä Marja; Kuittinen Taru; Penttilä Karri; Sikiö Anu; Savolainen Eeva-Riitta; et al. (WILEY, 2022)
Background Autologous stem cell transplantation (auto-SCT) is a widely used treatment option in multiple myeloma (MM) patients. The optimal graft cellular composition is not known.
Study design and methods Autograft cellular composition was analyzed after freezing by flow cytometry in 127 MM patients participating in a prospective multicenter study. The impact of graft cellular composition on hematologic recovery and outcome after auto-SCT was evaluated.
Results A higher graft CD34(+) cell content predicted faster platelet recovery after auto-SCT in both the short and long term. In patients with standard-risk cytogenetics, a higher graft CD34(+) count (>2.5 x 10/kg) was linked with shorter progression-free survival (PFS; 28 vs. 46 months, p = 0.04), but there was no difference in overall survival (OS) (p = 0.53). In a multivariate model, a higher graft CD34(+)CD133(+)CD38(-) (>0.065 x 10/kg, p = 0.009) and NK cell count (>2.5 x 10/kg, p = 0.026), lenalidomide maintenance and standard-risk cytogenetics predicted better PFS. In contrast, a higher CD34(+) count (>2.5 x 10/kg, p = 0.015) predicted worse PFS. A very low CD3(+) cell count (<= 20 x 10/kg, p = 0.001) in the infused graft and high-risk cytogenetics remained predictive of worse OS.
Conclusions Autograft cellular composition may impact outcome in MM patients after auto-SCT. More studies are needed to define optimal graft composition.